Roundtable: feminist interpreting (studies) - the story so far - Susam-Saraeva, Sebnem (2023)
This debate arose from my interest in translation and interpreting practices within maternal healthcare viewed from an ethical and feminist perspective, with a particular focus on advocacy. During the literature review, it quickly became obvious to me that, compared to feminist translation, research on feminist interpreting is scarce. My curiosity to find out what has been done in the field led me to reach out to colleagues with the relevant experience and to organise this roundtable discussion. The fact that I am not an interpreting studies scholar - despite having worked as an interpreter in the past - but a translation studies one with extensive experience in feminist frameworks enabled me to pose some provocative questions. I am very grateful to the colleagues who responded to my call for this discussion that we first carried out synchronously online. The result is a collaborative, polyphonic debate, which we hope will contribute to discussions of ethics in interpreting, attract attention to existing feminist interpreting practices and pave the way for a feminist interpreting studies.